Safety critical systems handbook : a straightforward guide to functional safety: IEC 61508 (2010 edition) and related standards : including: Process IEC 61511, Machinery IEC 62061 and ISO 13849 - Smith, David J. 1943 June 22- (Elsevier/Butterworth-Heinemann, 2011)
Electrical, electronic and programmable electronic systems increasingly carry out safety functions to guard workers and the public against injury or death and the environment against pollution. The international functional safety standard IEC 61508 was revised in 2010, and this is the first comprehensive guide available to the revised standard. As functional safety is applicable to many industries, this book will have a wide readership beyond the chemical and process sector, including oil and gas, power generation, nuclear, aircraft, and automotive industries, plus project, instrume.